Propuesta de optimización de los procesos operativos para el mejoramiento de la empresa National Cargo Express cia.ltda en la ciudad de Quito. - Villacis Almeida, Bryan Felipe (2022)
This research project focuses on the value-added processes in terms of the problems that were detected in the company National Cargo Express Cia.Ltda, since there is an inefficiency in the delivery of merchandise, which generates delays, losses, mishandling time and customer dissatisfaction; The objective of this work is to design a proposal for the optimization of operational processes for the improvement of the company focused on reducing resources and increasing the quality of its services, this research is of a descriptive type that allowed to participate directly with the company, starting from mainly in establishing the current state through observation, talks, records, time taking, process and procedure designs, even more with the help of the inductive method where particular situations such as poor planning and organization of loading and unloading were accurately identified. of the merchandise. Thanks to the study of times and methods used, an increase in efficiency was determined, in each operational process: in the reception of merchandise of 54.66%, in the loading of the merchandise to the road truck of 8.4% and for the last process There will be a double optimization with the unification of the last two current processes, saving an efficiency of 28.05%, resulting in an optimization of resources, good time management and an increase in the quality of your service.